Venezuelan University Network of Intellectual Property (RedUPIVen) Intellectual Property April 2022 (Gestión y Gerencia, 2022)
The purpose is to present the activities developed by the Venezuelan University Network of Intellectual Property (RedUPIVen) during the conference entitled "April of Intellectual Property". A set of webinars organized by the founding universities of the Network (Universidad Central de Venezuela, Universidad de Carabobo, Universidad Centroccidental  Lisandro Alvarado and the Parque Tecnológico Sartenejas of the Universidad Simón Bolívar) with the institutional support of allied universities such as the Universidad de Los Andes, Universidad of Zulia, Metropolitan and Monte Ávila Universidad. The syndemic generated by COVID-19 and its variants has led to maintaining remote presence as a valid alternative to spread knowledge and interact with intellectual property actors. 6 webinars were held with an attendance that easily exceeded a thousand national and foreign attendees, 25 national and 13 foreign speakers were presented, with institutional sponsorships from companies and international and national organizations such as ASIPI, FAO, CISAC, IIDA, SAPI, FRAP, among others. During the course, spaces were created for the productive exchange of knowledge around the new disruptive technologies and their impact on the regulation of intellectual property; without stopping looking retrospectively at its sources and its impact on the new modalities of protection of intellectual creations. Holding academic conferences of this nature contributes to the dissemination and transfer of knowledge.
Keywords: Venezuelan University Network of Intellectual Property; April events of Intellectual Property; Venezuela